Pengembangan buku olahraga sambo berbasis aplikasi digital untuk siswa di kegiatan ekstrakurikuler tingkat SMA - Br. Ginting, Elvita Ersama; Bangun, Sabaruddin Yunis; Siregar, Samsuddin (Universitas Nusantara PGRI Kediri, 2024)
The survey in North Sumatra was conducted by researchers in the areas of Medan, Tanah Karo, Tebing Tinggi, Asahan, Serdang Bedagai, Deli Serdang, Labuhan Batu, Tanjung Balai, Humbahas, and Binjai, many coaches and athletes still do not have adequate guidance in Indonesian. Most of the information is still in foreign languages, making it difficult to understand Sambo's techniques and rules. This study aims to develop a digital application-based sambo sports book. Method, in this research, uses the research and development (R&D) method. The research subjects consisted of 10 athletes, coaches, and sambo sports enthusiasts for the main field trial and 20 athletes, coaches, and sambo sports enthusiasts for the operational field trial. Data were collected through observation, interviews, and questionnaires, with instruments in the form of feasibility assessment sheets from sambo sports experts, linguists, media experts, and user subjects. Data analysis was carried out using a percentage quantitative descriptive technique. The results showed that this digital application-based sambo sports book was very good and feasible. This book has great potential to improve the understanding of sambo techniques and rules among athletes, coaches, and sambo enthusiasts by providing easy-to-understand guidelines in Indonesian and emphasizing the importance of technology-based approaches in Sambo.